Examining levels, distribution and correlates of healthinsurance coverage in Kenya - Kazungu1, Jacob S.; Barasa, Edwine W. (Published online in Wiley InterScience (www.interscience.wiley.com), 2017)
objectiveTo examine the levels, inequalities and factors associated with health insurance coveragein Kenya.methodsWe analysed secondary data from the Kenya Demographic and Health Survey (KDHS)conducted in 2009 and 2014. We examined the level of health insurance coverage overall, and bytype, using an asset index to categorise households into five socio-economic quintiles with quintile 5(Q5) being the richest and quintile 1 (Q1) being the poorest. The high–low ratio (Q5/Q1 ratio),concentration curve and concentration index (CIX) were employed to assess inequalities in healthinsurance coverage, and logistic regression to examine correlates of health insurance coverage.resultsOverall health insurance coverage increased from 8.17% to 19.59% between 2009 and2014. There was high inequality in overall health insurance coverage, even though this inequalitydecreased between 2009 (Q5/Q1 ratio of 31.21, CIX=0.61, 95% CI 0.52–0.0.71) and 2014 (Q5/Q1ratio 12.34, CIX=0.49, 95% CI 0.45–0.52). Individuals that were older, employed in the formalsector; married, exposed to media; and male, belonged to a small household, had a chronic diseaseand belonged to rich households, had increased odds of health insurance coverage.conclusionHealth insurance coverage in Kenya remains low and is characterised by significantinequality. In a context where over 80% of the population is in the informal sector, and close to50% live below the national poverty line, achieving high and equitable coverage levels withcontributory and voluntary health insurance mechanism is problematic. Kenya should consider auniversal, tax-funded mechanism that ensures revenues are equitably and efficiently collected, andeveryone (including the poor and those in the informal sector) is covered
full text
Keywords: health financing, health insurance, inequalities, Kenya